Food groups and urologic cancers risk: a systematic review and meta-analysis of prospective studies - Qi, Jingyi; An, Peng; Jin, Dekui; Ji, Yuting; Wan, Sitong; Zhang, Xu; Luo, Yongting; Luo, Junjie; Zhang, Chengying (Frontiers in Nutrition, 2023)
Background To assess the association between 12 food groups intake and the risk of urologic cancers. Methods We scanned PubMed and Web of Science databases up to April 1st, 2023, and 73 publications met the inclusion criteria in the meta-analysis. We used a random effects model to estimate the summary risk ratios (RRs) and 95% confidence intervals (95% CI). Results In the linear dose–response meta-analysis, an inverse association was found between each additional daily 100 g of fruits [RR: 0.89, 95%CI = (0.83, 0.97)], 100 g of vegetables [RR: 0.92, 95%CI = (0.85, 0.99)], 12 g of alcohol [RR: 0.91, 95%CI = (0.88, 0.94)] and 1 cup of coffee [RR: 0.95, 95%CI = (0.83, 0.97)] intake and the risk of renal cell carcinoma. Conversely, each additional daily 100 g of red meat intake was positively associated with renal cell carcinoma [RR: 1.41, 95%CI = (1.03, 2.10)]. Inverse associations were observed between each additional daily 50 g of egg [RR: 0.73, 95%CI = (0.62, 0.87)] and each additional daily 1 cup of tea consumption and bladder cancer risk [RR: 0.97, 95%CI = (0.94, 0.99)]. There were no significant associations for nonlinear dose–response relationships between 12 food groups and urological cancers. Conclusion Our meta-analysis strengthens the evidence that appropriate intake of specific food groups, such as fruits, vegetables, alcohol, tea, and coffee, is associated with the risk of renal cell carcinoma or bladder cancer. More studies are required to fill the knowledge gap on the links between various food groups and urologic cancers because the evidence was less credible in this meta-analysis. Systematic Review Registration This study was registered on PROSPERO (CRD42022340336).